Análisis de cumplimiento de las obligaciones tributarias para determinar las contingencias en el período fiscal desde el 1 de enero a 31 de diciembre del 2008 de una empresa dedicada a la elaboración de prefabricados de hormigón - Wonsang Valle, Carol Ivonne (2009)
The constant legal reforms and the tax burden to which the contributors are submitted, carry frequently to incurring mistakes or omissions for ignorance or meaningful, which, they stem in tributary contingencies or overpayments of taxes. The companies constant demand of tools that it allows them to evaluate the suitable fulfillment of the tax debts and the razonabilidad of the amounts that are recorded in the annual declaration of the Tax to the Revenue, as well as of other taxes and taxes retained to third. The analysis by means of the evaluation of the concepts that integrate the tax bases and of the criteria established by the Tributary Administration it allows establishing the regulation existence of crimes of cheating, tributary infractions, breaches or mistakes. The present work constitutes a review of the expense accounts and income that appear in the State of Results and General Balance to check that the tax bases, credits, rates and taxes are due applied and sustained, to check that the declared information corresponds to the operations annotated in the countable records and to the economic effected transactions and to identify possible contingencies and tributary infractions in the fiscal year 2008. To reach the aims established in this review substantive proofs were applied to the items of the financial statements that are considered in the production(elaboration) of the Tributary Conciliation of the Tax to the Revenue of 2008 generating, across instruments of compilation of information and analysis of works papers, a letter of recommendations for the management of the demonstrated contingencies that constitute a cheating to the active subject, in which actions are included for possible improvements in the countable system in the tributary checked aspects.